2014
DOI: 10.3109/09273948.2013.870213
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Evaluation of Efficacy and Safety of Deep Sclerectomy in Uveitic Glaucoma

Abstract: DS is safe and effective in patients with uveitic open-angle glaucoma. However, laser goniopuncture is frequently needed to improve the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…As summarised in Table 3, we identified three case series specific to NPGS in UG after an extensive online search using Medline and EMBASE. [26][27][28][29] The mean follow-up in these case series varied from 12 to 46 months with unqualified success (for IOP o21 mm Hg) ranging from 45 to 85% of cases within those time frames. No cases of bleb-related infection or delayed hypotony were reported in these series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarised in Table 3, we identified three case series specific to NPGS in UG after an extensive online search using Medline and EMBASE. [26][27][28][29] The mean follow-up in these case series varied from 12 to 46 months with unqualified success (for IOP o21 mm Hg) ranging from 45 to 85% of cases within those time frames. No cases of bleb-related infection or delayed hypotony were reported in these series.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] In UG, encouraging preliminary results have been reported for both DS and viscocanalostomy. [26][27][28][29][30] Our study highlights the clinical outcomes, complications, and failure rates for augmented deep sclerectomy in UG and compares these to the current published literature on both deep sclerectomy and augmented trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that deep-sclerectomy is an effective and reliable method in patients with steroidinduced glaucoma in the presence of an accompanying inflammatory eye disease such as uveitis and in patients undergoing penetrating keratoplasty (29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…ODR has been shown to occur primarily after a trabeculectomy or glaucoma drainage devices, but rarely after an uncomplicated DS [2]. It is more common in uveitic [3] and exfoliation glaucoma [4]. A multifocal hemorrhagic retinopathy, which is not accounted for by other processes, can also be seen.…”
Section: Discussionmentioning
confidence: 99%